Syair al-Hikmah wa al-Mauidzoh Fi Diwan Mahmud al-Warraq (Analisis Semiotika Riffaterre) - Muhammad Dedad Bisaraguna Akastangga (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2020)
Literary works make language the medium, because through the language of writers imagining their thoughts and ideas. Poetry genre is a literary genre. Poetry explains something with something else. In other words there are indirect expressions in poetry. This research is titled poem al-Hikmah wa al-Mauidzoh Fi Diwan Mahmud al-Warraq with a Semiotic analysis knife proposed by Michael Riffaterre. The method used in this research is descriptive qualitative. The results of this study are based on heuristic reading, it means that a human being must forgive one another's mistakes, even though there are so many mistakes. In the hermeneutic reading, it means that a judge who requires himself to forgive the mistakes of others, then described three types of judges namely the noble, the lowly judge, and a good judge or comparable to a noble judge. The model is found in four sentences namely